Geografia(s), saberes, práticas e vivências culturais de jovens adolescentes - Greco, Fatima Aparecida da Silveira (2000)
This work deals with school Geography, learners and learning. Having pupils learning interest as one of the main difficulties teachers face up to in the classrooms at the moment, this study tries to discuss the relationship between students and school Geography approaching themes such as the historical-cultural subject, youth culture, media, space, world and globalization. Analyzing Geography as a knowledge and moving practice and constituting the elementary school last grade students as subjects of this analysis, I focus on their spatial practices and cultural way of living, in and out school environment. Delineating the student as a human being in his multiple dimensions, in his process of adolescence and being youth in contemporary word, spaces and means of communication are mapped to see where these 14-17-year-old adolescents, - which are social and culturally heterogeneous, living in different neighborhoods -, spend their time, space and world. Also the reading these 5th. -8 th. grade students do of taught and learned Geography in the public schools, is analyzed. The configuration of a multicultural web of identity references, language, pedagogical discourses and youth cultural expressions present in Geography and lived by these adolescents contrasts with the language, practicing and Geography contents of school curriculum, providing clues to understand why adolescents put in evidence that although they recognize the importance of Geography, the discipline does not motivate their interest. This disproportion of time-space between the in and out school world shows the necessity of a discussion on the curriculum issues regarding formcontent, and theory-practice specially in the Geography teaching/learning process. It s necessary to establish a teacher-student dialogue and also a coherent geographical knowledge with adolescents time-space in contemporary world to provide them with an overcoming of common sense knowledge facing the apparent realities of social environment.